MODIFICATION AND EVALUATION OF SEEDLING PICKING AND RELEASING MECHANISM OF ANNAPURNA RICE TRANSPLANTER - MRINMOY BISWAS*, E.V. THOMAS; UTTAM KUMAR (The Journal of Research ANGRAU, 2019)
The Laboratory model seedling picking and releasing mechanism has been developed by modifying the mechanism of “Annapurna Rice Transplanter”during 2012-13. Opening of finger is controlled by gap provided between two T-shaped cam plates. Finger assembly has two arms, shorter arm is attached to the fixed L-angle bar and longer arm was hinged to the fixed shaft. Both arms are connected by a spring. Spring is used to close the finger after picking the seedling from the seedling tray. Two channels mounted on the frame are also provided for the smooth movement of finger assembly. One channel has straight path through which finger assembly can be raised or lowered for holding the cluster of seedlings and another is curved path through which finger assembly can be lowered for releasing of seedling. Two roller sets were used to guide the movement of cam during the picking and planting operations. The Laboratory model manual rice transplanter was tested for its picking and releasing operation of seedlings in the laboratory conditions. Opening width of fingers increased linearly with the depth of handle from its reference level allowing smooth operation of opening and closing of fingers while picking and releasing of a cluster of seedlings.